Applications of multimodal concordances - Baldry, Anthony; Thibault, Paul J. (HERMES - Journal of Language and Communication in Business, 2008)
Multimodal corpus linguistics has so far been a theoretical rather than an applicative discipline. This paper sketches out proposals that attempt to bridge between these two perspectives. It does so with particular reference to the development of the conceptual and software tools required to create and concordance multimodal corpora from the applicative standpoint and as such is designed to underpin the study of texts at universities in foreign-language teaching and testing cycles. One branch of this work relates to multimedia language tests which, as illustrated in Section 2, use concordancing techniques to analyze multimodal texts in relation to students’ understanding of oral and written forms of discourse in English. Another branch is the exploration of multimodal tests concerned with the explicit assessment of students’ knowledge of the principles and/or models of textual organization of multimodal texts. The two types of test are not mutually exclusive. A third branch of research thus relates to the development of hybrid tests which, for example, combine a capacity to analyze multimodal texts with an assessment of students’ language skills, such as ﬂuency in speaking and writing in English or which ascertain the multimodal literacy competencies of students and the differing orientations to meaning-making styles that individuals manifest. The paper considers these different applicative perspectives by describing the different categories of concordance achievable with the MCA online concordancer (Section 2) and by deﬁning their relevance to multimodal discourse analysis (Section 3). It also illustrates the use of meaning-oriented multimodal concordances in the creation and implementation of multimodal tests (Sections 4). It concludes by suggesting that the re-interpretation of the nature and functions of concordances is long overdue and that the exploration of new types of concordance is salutary for linguistics and semiotics in general.